Utilization of Instagram @kominfodiy as Publication and Information Media for the Department of Communications and Informatics of the Special Region of Yogyakarta - Harsyid, Ahmad Ridho; Lestari, Rani Dwi; Awola, Eunike Dina (Formosa Journal of Applied Sciences, 2025)
The study used the Circular Model Of Some theory from Regina Luttrel which explains planning in using social media using 4 stages, namely share, manage, optimize and engage. From the data found, the DIY Communication and Information Office utilizes Instagram features as well as possible by distributing quality information and educational content, approaching followers in a responsive and responsive manner and having transparency to the community, approaching followers with the call "lurr ", packaging content according to the target audience and collaborating with other agencies. The use of Instagram @kominfodiy in publication and information media is indeed good and optimal, although there are still shortcomings, namely the production of too much content, resulting in less than optimal content.